Level of tumor-infiltrating lymphocytes and density of infiltrating immune cells in different malignancies - Castañeda, Carlos A. (2019)
Aim: To correlate levels of tumor-infiltrating lymphocytes (TIL) evaluated using the International Immuno-Oncology Biomarker Working Group methodology, and both density of tumor-infiltrating immune cell and clinicopathological features in different malignancies. Methods: 209 pathological samples from gastric cancer, cervical cancer (CC), non-small-lung cancer, cutaneous melanoma (CM) and glioblastoma were tested for TIL in hematoxylin eosin, and density of CD3+, CD4+, CD8+, CD20+, CD68+ and CD163+ cells by digital analysis. Results: TIL levels were higher in invasive margin compartments (IMC). TIL in IMC, intratumoral and stromal compartments predicted survival. CC and gastric cancer had higher TIL in intratumoral; CC and CM had higher TIL in stromal compartment and IMC. CM had the highest density of lymphocyte and macrophage populations. CD20 density was associated with survival in the whole series. Conclusion: Standardized evaluation of TIL levels may provide valuable prognostic information in a spectrum of different malignancies.